EOLES Project...Teaching Unit experiences - Fidalgo, André Vaz (2015)
EOLES is an international cooperative project, with an emphasis not only on one of the facets of engineering education, but trying to involve all of them. This paper describes the course’s accreditation, the structure the E-learning framework, the virtual and remote laboratories integration in the course and focuses on the experiences with one of the Teaching Units. Some data related to the first edition of the course is provided, as well as an initial analysis of the learning results and experiences. The accreditation and validation efforts are also introduced and discussed. The EOLES course is the result of an international effort involving experts from different engineering and education areas, in order to provide a better global Engineering Education.